Sosialisasi dan Pendampingan Pentingnya NIB untuk UMKM Kelurahan Gunung Anyar secara Door to door - Alief Indy Millani; Elvira Dewanti Libragiantar; Dimas Maulana Putra; Abyaan Basyaar Roofif; Rafi Fahrezi Asmynendar (Jurnal Masyarakat Mengabdi Nusantara, 2023)
NIB is an official identity given by the government to UMKMs as a form of recognition and legal protection for the business being run. Therefore, socialization activities were carried out on the importance of Nomor Induk Berusaha (NIB) for Micro, Small and Medium Enterprises (MSMEs) in Gunung Anyar Village. The research method used is door to door, namely by visiting MSME owners directly in Gunung Anyar Village to provide socialization about the importance of NIB. This socialization also provides an opportunity for MSME owners to ask questions and get clarification regarding NIB registration procedures and steps that must be taken to obtain them. It is hoped that the results of this research can increase the understanding and awareness of MSME owners in Gunung Anyar Village about the importance of NIB and encourage them to take care of NIB as a strategic step in developing their business.